Digital Communication, Artificial Intelligence, and The Transformation Of Law Enforcement In Indonesia: Challenges and Regulatory Response - Musdalipa R; Juangsah Juangsah; Jalil B (Jurnal Ilmu Sosial dan Humaniora, 2026)
The rapid development of digital communication supported by Artificial Intelligence (AI) has transformed the dynamics of law enforcement in Indonesia; however, studies that integrate the influence of digital communication, AI challenges, and regulatory responses within a single comprehensive analytical framework remain limited. This study aims to analyze the influence of digital communication on the formation of public opinion, the impact of disinformation, hoaxes, and deepfakes, the risks of algorithmic bias and ethics, regulatory gaps, and adaptive strategies in AI-based law enforcement. The study employs a library research method with a qualitative descriptive approach. Analysis was conducted using content analysis techniques through the grouping of data into five main themes, namely digital communication and public opinion, disinformation and deepfakes, algorithmic bias and AI ethics, regulatory gaps, and adaptive strategies in AI-based law enforcement. The findings indicate that digital communication plays an important role in shaping public opinion toward legal processes; disinformation, hoaxes, and deepfakes threaten the effectiveness and integrity of evidence; the use of AI has the potential to generate algorithmic bias and ethical issues; AI implementation still faces regulatory gaps in Indonesia; and adaptive strategies are required through the strengthening of legal frameworks, enhancement of digital forensic capacity, application of human oversight, strengthening of public digital literacy, and the application of algorithmic transparency and accountability standards. This study provides a theoretical contribution by integrating the perspectives of digital communication, artificial intelligence, and law enforcement within a single analytical framework, as well as a practical contribution as a basis for the formulation of transparent, accountable, and just AI policies and governance within the law enforcement system in Indonesia.